Hedgehog signaling regulates telomerase reverse transcriptase in human cancer cells. - Tapati Mazumdar; Ranjodh Sandhu; Maha Qadan; Jennifer DeVecchio; Victoria Magloire; Akwasi Agyeman; Bibo Li; Janet A Houghton (PLoS ONE, 2013)
The Hedgehog (HH) signaling pathway is critical for normal embryonic development, tissue patterning and cell differentiation. Aberrant HH signaling is involved in multiple human cancers. HH signaling involves a multi-protein cascade activating the GLI proteins that transcriptionally regulate HH target genes. We have previously reported that HH signaling is essential for human colon cancer cell survival and inhibition of this signal induces DNA damage and extensive cell death. Here we report that the HH/GLI axis regulates human telomerase reverse transcriptase (hTERT), which determines the replication potential of cancer cells. Suppression of GLI1/GLI2 functions by a C-terminus truncated GLI3 repressor mutant (GLI3R), or by GANT61, a pharmacological inhibitor of GLI1/GLI2, reduced hTERT protein expression in human colon cancer, prostate cancer and Glioblastoma multiforme (GBM) cell lines. Expression of an N-terminus deleted constitutively active mutant of GLI2 (GLI2ΔN) increased hTERT mRNA and protein expression and hTERT promoter driven luciferase activity in human colon cancer cells while GANT61 inhibited hTERT mRNA expression and hTERT promoter driven luciferase activity. Chromatin immunoprecipitation with GLI1 or GLI2 antibodies precipitated fragments of the hTERT promoter in human colon cancer cells, which was reduced upon exposure to GANT61. In contrast, expression of GLI1 or GLI2ΔN in non-malignant 293T cells failed to alter the levels of hTERT mRNA and protein, or hTERT promoter driven luciferase activity. Further, expression of GLI2ΔN increased the telomerase enzyme activity, which was reduced by GANT61 administration in human colon cancer, prostate cancer, and GBM cells. These results identify hTERT as a direct target of the HH signaling pathway, and reveal a previously unknown role of the HH/GLI axis in regulating the replication potential of cancer cells. These findings are of significance in understanding the important regulatory mechanisms that determine the functions of HH/GLI signaling in cancer cells.